The Effect of Addition Electrical Supercharger on Diesel Dual Fuel Engine with Variation of Air Mass Flow Rate to The Engine Performance and Emissions - Jamaludin Jamaludin; Dori Yuvenda; Bambang Sudarmanta (Institut Teknologi Sepuluh Nopember, 2019)
Diesel Dual fuel system is a diesel operated by using dual fuel CNG and diesel fuel as a pilot fuel. The problem that often occurs in dual fuel system is the reduced ratio of air and fuel. This causes the thermal efficiency to be lower. So in this study mounted electric supercharger as an air supply for performance and efficiency, and emissions from diesel engines better. This research uses diesel engine type Diamond Di 800 with dual fuel indirect injection model system. The method used is to vary the air mass flow rate (ṁ) through intake manifold to the combustion chamber 0.0063 kg/s, 0.0072 kg/s, 0.0077 kg/s, 0.0087 kg/s, and 0.0095 kg/s by adjusting the voltage on electric supercharger 8V, 9V, 10V, 11V, and 12V. Measurements are made to: the current and the voltage of each load, the consumption time of 25 ml diesel fuel, and the exhaust emissions (CO, HC, and PM). The best result was found that the addition of air mass flow rate (ṁ) to dual fuel system had no significant effect on the engine's effective power, torque, Bmep when compared with single fuel. The addition of air mass flow rate (ṁ) 0.0087 kg/s can substitution the diesel fuel by 56.45%, thermal efficiency increased by 33.57% but under single fuel condition, and increase the average AFR by 64.31%. The average CO and HC emissions decreased by 15.18% and 62.35% even though they were under single fuel condition, while the PM emissions increase with increasing loads but compared to single fuel decreased by 75%